Creativity and Emotional Intelligence. (How to develop emotional competence, in Preschool, through linguistic expression and body language). - Cruz Cruz, Purificación (Historia y Comunicación Social, 2014)
It is important to put into reach amongst the pupils of Preschool all the different types of language which will serve them to express their emotional world, since it is the stage of maximum expressivity: body language, musical language, plastic language, verbal and non-verbal language and symbolic game. For this reason, teachers must learn to manage the emotions and social abilities of their pupils in their classrooms developing their Emotional Intelligence in a creative, playful and entertaining manner.
Keywords: Emotional intelligence; expressivity; theatrical game; preschool.